An intra-individual analysis of players' perceived coaching behaviours, psychological needs, and achievement goals - Wang, C.; Koh, K.; Chatzisarantis, Nikos (Multi-Science Publishing Co. Ltd., 2009)
The purpose of this study was to examine the relations between perceptions of coaching behaviours, psychological needs, achievement goals and motivational indicators (enjoyment and effort) at an intra-individual level. A total of 264 high-school basketball players aged between 14 to 17 years old from 19 schools in Singapore took part in the study. The participants completed a battery of questionnaires measuring perceived coach's leadership style, achievement goals, behavioural regulations and competence, needs satisfaction, and enjoyment. Cluster analysis found 3 distinct groups differing in perceived coaching behaviours among the basketball players. The three clusters differed significantly on the indices of intrinsic motivation, perceived needs satisfaction, and achievement goals. This study shows that distinct groups of players could be identified in terms of perceived coaching behaviours and these perceptions may impact the amount of enjoyment and effort exerted during training and competition, perceived competence, achievement goals and autonomy.